2018
DOI: 10.1194/jlr.r082933
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic role of the transmembrane glycoprotein CD36 (SR-B2) in cellular fatty acid uptake and utilization

Abstract: The widely expressed transmembrane glycoprotein CD36, a scavenger receptor class B protein (SR-B2), serves many functions in lipid metabolism and signaling. Here, we review CD36's role in facilitating cellular long-chain fatty acid uptake across the plasma membrane, particularly in heart and skeletal muscles. CD36 acts in concert with other membrane proteins, such as peripheral plasma membrane fatty acid-binding protein (FABP pm ), and is an intracellular docking site for cytoplasmic fatty acid-binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
216
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(225 citation statements)
references
References 78 publications
4
216
2
3
Order By: Relevance
“…27,28 CD36/SR-B2 is a class B scavenger receptor that shows high affinity for long-chain FA. 29 CD36 is considered to concentrate FA within specific plasma membrane domains and increase fatty acid availability for subsequent membrane translocation. Several studies have shown that CD36 increases fatty acid uptake in beta cells.…”
Section: Intracellular Lipid Metabolites As Regulators Of Insulin Secmentioning
confidence: 99%
“…27,28 CD36/SR-B2 is a class B scavenger receptor that shows high affinity for long-chain FA. 29 CD36 is considered to concentrate FA within specific plasma membrane domains and increase fatty acid availability for subsequent membrane translocation. Several studies have shown that CD36 increases fatty acid uptake in beta cells.…”
Section: Intracellular Lipid Metabolites As Regulators Of Insulin Secmentioning
confidence: 99%
“…The transport of these fatty acids into the requiring tissues is facilitated by the fatty acid transporter CD36 present in the plasma membrane. This role of CD36 is reviewed by Glatz and colleagues (8). CD36 is a member of the family of class B scavenger receptors (SRB-2).…”
Section: Transfer Of Lipid From Diet To Tissuementioning
confidence: 99%
“…One such transporter examined is the fatty‐acid translocase or cluster of differentiation 36 ( Cd36 ) classified as a scavenger receptor class B protein (SR‐B2). This fatty‐acid transporter has been found not to be well expressed in the liver and appears to be much more readily expressed in other energy‐utilizing tissues like heart and adipose tissues (Glatz and Luiken, ). However, upon treatment with fenofibrate, the hepatic mRNA levels of Cd36 were significantly increased (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%